2016
DOI: 10.1093/pubmed/fdw040
|View full text |Cite
|
Sign up to set email alerts
|

The role of parental smoking on adolescent smoking and its social patterning: a cross-sectional survey in six European cities

Abstract: Adolescents are more likely to smoke when their father and mother smoke. Although the susceptibility to parental smoking was similar across social classes, SE differences in parental smoking contribute to the transmission of SE inequalities in smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
23
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 28 publications
9
23
0
3
Order By: Relevance
“…Furthermore, the fact that parental smoking status moderated biases toward smokers is broadly consistent with the finding that this status predicts risk factors for tobacco dependence itself (e.g., Alves et al, 2016;Distefan et al, 1998;Murray et al, 1985). Helsinki declaration and its later amendments or comparable ethical standards.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Furthermore, the fact that parental smoking status moderated biases toward smokers is broadly consistent with the finding that this status predicts risk factors for tobacco dependence itself (e.g., Alves et al, 2016;Distefan et al, 1998;Murray et al, 1985). Helsinki declaration and its later amendments or comparable ethical standards.…”
Section: Discussionsupporting
confidence: 73%
“…One possible explanation is that some non-smokers, especially adolescents, reside in families with smokers. Indeed, much previous research has indicated that parental smoking identity impacts the smoking behavior of their offspring (e.g., Alves et al, 2016;Andrews, Hops, & Duncan, 1997;Distefan, Gillpin, Choi, & Pierce, 1998;Wang, Hipp, Butts, Jose, & Lakon, 2016).…”
Section: Assessing the Impact Of Parental Smoking Status (Studies 1 Amentioning
confidence: 99%
“…The negative association found between OSY smoking and parent smoking in this study may appear to be contradictory with the literature. However, applying a simple logistic regression with self-smoking as dependent variable and parent smoking as a predictor variable result in a positive zero-order association, confirming what has been found in previous studies (159)(160)(161)(162)(163)(164)(165)(166). What our results show is that, once this association is controlled for potential confounders such as OSY friend smoking, the association becomes negative.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, we controlled our models for other sociodemographic variables, all of which have been found to be related to smoking [42][43][44]. First, we controlled for age ("How old are you?…”
Section: Friends' Influence (G) Getting Into Trouble (G)mentioning
confidence: 99%